2012
DOI: 10.1128/aem.00186-12
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian Sheep Are an Important Reservoir for Human-Pathogenic Escherichia coli O26:H11

Abstract: ABSTRACTA previous national survey ofEscherichia coliin Norwegian sheep detectedeae-positive (eae+)E. coliO26:H11 isolates in 16.3% (80/491) of the flocks. The purpose of the present study was to evaluate the human-pathogenic potential of these ovine isolates by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…Although the withinherd prevalence was low, previous research reported that 90% of Australian sheep farms had animals testing positive for STEC (46). In Norway, however, the risk of human infection from sheep was much more significant since almost 50% of the sheep O26 isolates had multiple-locus variable number tandem repeat analysis profiles similar to that found in human clinical cases (35). The importance of sheep in STEC epidemiology was also demonstrated by Oporto et al (47), who reported that greater than 50% of sheep herds in Spain had animals shedding non-O157 STEC compared to 20.7% in dairy cattle and 46% in beef cattle.…”
Section: Small Ruminantsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the withinherd prevalence was low, previous research reported that 90% of Australian sheep farms had animals testing positive for STEC (46). In Norway, however, the risk of human infection from sheep was much more significant since almost 50% of the sheep O26 isolates had multiple-locus variable number tandem repeat analysis profiles similar to that found in human clinical cases (35). The importance of sheep in STEC epidemiology was also demonstrated by Oporto et al (47), who reported that greater than 50% of sheep herds in Spain had animals shedding non-O157 STEC compared to 20.7% in dairy cattle and 46% in beef cattle.…”
Section: Small Ruminantsmentioning
confidence: 88%
“…Although cattle have been identified as the major reservoir for STEC in the United States, small ruminants play a greater role in the epidemiology of STEC infections in other countries. For example, sheep have been identified as the host of significance in Australia (1) and have also been recognized as an important reservoir of STEC O26 in Norway (35). In addition to STEC serogroups O157 and O26, sheep have been cited as reservoirs for more than 100 other serotypes of STEC, including O115, O128, and O130 (34,35) Transmission of STEC to small ruminants occurs through the same pathway as in cattle.…”
Section: Small Ruminantsmentioning
confidence: 99%
“…Confirmation of stx 1 , stx 2 , and eae was done at the National Reference Laboratory for Enteropathogenic Bacteria (NRL) at the NIPH (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of naturally occurring VTEC has been widely reported in sheep, and studies indicate that sheep feces and sheep meat are important reservoirs of human pathogenic VTEC (49)(50)(51)(52)(53)(54)(55). Seasonal prevalence of VTEC in sheep has been reported (54,56), with incidences peaking in summer months in a similar trend to that in cattle and human infections (45).…”
Section: Carriage Of Vtec In Sheep and Goatsmentioning
confidence: 70%